JURIDICAL ANALYSIS OF LAW ENFORCEMENT OF THE DISCRETION EFFORTS RESEARCH IN POLRESTA BARELANG - Kaspol Jihad (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Circulation is increasingly widespread in the current case of drug abuse, and the mode of operation is increasingly diverse; the police must develop their own law enforcement strategies. However, there is also a need for some form of supervision and control of actions policing to reduce the possibility of abuse of discretion so that the negative impact of implementing the discretion does not result in injustice. The law only contains the basic rules in practice enforcement, which always depends on the community context. Therefore The police are given the authority to exercise police discretion, a concept giving authority to take actions based on careful consideration of the conscience of the police on duty or the consideration of police institutions. This study aims to determine how law enforcement is above the Circulation of methamphetamine-type narcotics through discretionary efforts factors that become obstacles/obstacles to Law Enforcement on Circulation Narcotic Type of Methamphetamine Through Discretionary Efforts. This research uses empirical normative legal research is legal research that uses Secondary data sources combined with legal research that uses primary data sources The results of the study show that the factors that influence the implementation of police discretion in solving criminal cases, narcotics, legal substance factors, namely the existence of a legal basis give authority to members of the police to take action discretion so that the implementation of the task does not harm the context of law enforcement and must be done professionally and by the police code of ethics as must for police officers, given the power of discretion without being accompanied restrictions can potentially abuse authority. For this reason, the discretion taken by the investigator must be aimed at getting a sense of fairness even though it is not contained in the Criminal Code will but, in essence, to maintain legal certainty and internal order Public.